Pelatihan Kepemimpinan di Lingkungan Organisasi OSIS SMK Tarakanita - Ponziani, Regi Muzio; Putri, Ade Hanifa; Nellyana; Hidayat, Muwafick; Suparmun, Haryo; Soegijanto, Cleophila M.G.T. (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2025)
The community service program aims to explain and train the candidates of OSIS members including the chairs, the concept of leadership and GRIT. The program was implemented on January 20, 2025 at SMK Tarakanita Jakarta. The speakers and trainers involved two lecturers from STIE Trisakti (Sekolah Tinggi Ilmu Ekonomi Trisakti) and two senior students. The participants were 37 students intended to be the members of OSIS. The program was divided into lecturing and interactive sessions. The lecturing session was presented by the lecturers explaining the concept of leadership, GRIT, and the qualities of good leaders. During the lecturing session, the speakers also convey some questions to the students to confirm the comprehension of the participants. Subsequent to the lecturing session, two senior university students held the interactive sessions. In this session, the speakers shortly talked about personality and personality test such as MBTI. Participants were again asked some questions and answers some quizzes. The students were then given prizes for the best answers. Future community service program could further the leadership issues by conducting role play methodology.